Singularidades da Educação na Colônia Agrícola Japonesa de Santa Cruz - Souza, Sinvaldo do Nascimento (2005)
We can present the result of research that the object will be analyze the singularities of education and the culture in the agricultural colony Japanese of Santa Cruz, situated in the west side of Rio de Janeiro. The education theme constitute on this. The research verifies a lot of visits to residence, with tape recording and consultation of literature about the theme. Presents with argumentation the trajectory of Nipo-Brasileiros at rural schools, your presence in physical space of the school, your desire for better education and better teaching and with this strategy allowed the success of all community and yours integral in particular. For comprehension the object of study, made necessary apprehension or emphasize about Japanese immigration in Brazil. For this, the agricultural colony Japanese was localized historical and geographical. It is finishing that it presents a particular and proper formation in Santa Cruz since 1938. Exception that in academy level, it treats the just research about a small Japanese colony established for thirty six families, accommodated since 1938, between the government Vargas of Cotia, in an area historic and geographic enough significant.